Serotonin and aggressive behaviour in children and adolescents: a systematic review. (24th January 2019) - Runions, K. C.; Morandini, H. A. E.; Rao, P.; Wong, J. W. Y.; Kolla, N. J.; Pace, G.; Mahfouda, S.; Hildebrandt, C. S.; Stewart, R.; Zepf, F. D.
Abstract : Objective: The role of serotonin (5‐HT) in human aggression has been the subject of a large number of studies, mostly with adults. Meta‐analyses indicate a small but significant inverse relationship between central nervous 5‐HT availability and aggression, but genetically informed studies suggest two pathways: one to reactive aggression and the other to proactive aggression. Method: We conducted a systemic review on central nervous 5‐HT function in children and adolescents, with attention to the function of aggression. Results: In total, 675 articles were screened for relevance, with 45 reviewed. These included blood assays (e.g. plasma, 5‐HIAA; platelet 5‐HTR2A ), epigenetic studies, retrospective PET studies and 5‐HT challenge paradigms (e.g. tryptophan depletion). Overall, findings were mixed, with support both for negative and for positive associations of central nervous 5‐HT function with aggression in children and adolescents. Conclusion: We propose factors that may be blurring the picture, including problems in the conceptualization and measurement of aggression in young people, the lack of prospective designs and the bias towards clinical samples of boys. Research needs to account for variance in the both motivation for and implementation of aggression, and look to the behavioural economics literature to consider the roles of reward, vengeance and self‐control more clearly.